Morombo’esara Nhebo’e: o aprender e o ensinar do professor indígena potiguara na Baía da Traição/Paraíba - Santos, Pedro Lôbo dos (2021)
This research aims to analyze the continuing education offered to indigenous teachers, identifying their contribution to Indigenous School Education of the Potiguara-PB People from the experience at the Escola Estadual Indígena de Ensino Fundamental e Médio Pedro Poti, located in Aldeia São Francisco, in the municipality of Baía da Traição-PB. Based in the legislation that regulates Indigenous School Education as a legitimate modality, it is necessary to dialogue with indigenous teachers and their framework of knowledge and practices that relate to our culture and tradition, based on the indigenous reality, enabling the dialogue of popular knowledge and scientific knowledge, promoting the right to cultural diversity that is a common heritage of humanity. This investigation is methodologically configured as qualitative research, having as theoretical foundations the perspective of popular education the studies of Brandão (2005), Freire (1996), Streck and Esteban (2018), of decolonial intercultural education with Quijano (2010), Fanon ( 2015), Santos (2010), Collet (2006) and Candau (2008; 2016 and 2018) and indigenous education with Munduruku (2002, 2012; 2019), Bonin (2012), Bergamaschi and Silva (2007), Arritu (1995 ), Barcellos (2012) and Nascimento (2012), Baniwa (2006), in addition to the National Curriculum Framework for Indigenous Schools (RCNEI-1998) and the National Curriculum Guidelines for Indigenous School Education (2013). We work with document analysis and thematic content analysis in dialogue with Cellard (2008), Flick (2009) and Bardin (2011). As a result, we verified the protagonism of the collective of indigenous educators, conquering new curricular proposals for schools in Potiguara villages in Paraíba. Indigenous School Education from the perspective of Popular Education presents itself as “viable unprecedented”, an expression of the resistance of our People through critical political-pedagogical education.